EFFECT OF USING CHEMICALLY TREATED BARLEY ON MILK PRODUCTION & COMPOSITION AND SOME BIO-CHEMICAL CHARACTERISTICS IN CROSS BRED FRESIAN CATTLE - Kassem M. M (Mesopotamia Journal of Agriculture)
This study has been achieved in the field of the agricultural college in Salah-Aldeen University, to investigate the effect of using barley treated with formaldehyde (9 liter/ ton) with Soya bean meal or urea in feeding hybrid dairy cows (fresian x karadi) with barley straw ad libtum on milk production and composition . 4 cows were used with 4 experimental rations and 4 periods (3 weeks each) using (4 × 4) latin square design. The 1st ration contained untreated barley with Soya bean meal (UB + SBM), the 2nd formaldehyde treated barley with Soya bean meal (TB+SBM), the 3rd ration (UB + urea) and the 4th ration (TB + urea). Cows consumed similar quantities of dry matter. There were no significant differences in average daily milk production which was 9.62, 9.79, 9.31, 8.76 kg/day for the 4 treatments respectively. There was a significant decrease in milk fat content when treated barley was fed with either Soya bean meal or urea as compared with untreated barley (3.75, 3.60, 3.52, and 3.40% respectively). There was a significant decrease in milk fat % in the treatments that contained urea compared with those containing soya bean meal, also significant increase in the average milk fat yield 14% with the both treatments that contained soya bean meal compared with those containing urea. Treating barley with formaldehyde resulted in a significant increase in milk protein % with either soya bean meal or urea 4.00 & 3.46% respectively. Also milk protein % significantly increased with rations containing Soya bean meal as compared with rations containing urea. As a result there was a significant increase in daily milk protein yield 24% in treatments containing soya bean meal compared with those containing urea. Finally a significant increase in lactose yield was registered with the treatment (TB + SBM) compared with the treatment (TB + Urea).